Pemanfaatan Desmos untuk Pembelajaran Matematika Interaktif bagi Guru Matematika SMK di Salatiga - Lulu Choirun Nisa; Ayus Riana Isnawati; Ariska Kurnia Rachmawati; Seftina Diyah Miasary (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
Desmos is a web-based platform that offers interactive mathematical tools, primarily a graphing calculator, to dynamically visualize mathematical concepts. Using Desmos is one solution to the challenges of teaching mathematics, which often lacks engagement and interactivity due to its abstract nature. Mathematics teachers from vocational schools across Salatiga have received training on utilizing Desmos in teaching. As a result, 85% of participants found Desmos easy to use, 80% felt that Desmos significantly aids mathematics teaching, particularly in visualizing concepts, 76% stated that the Desmos Graphing Calculator makes graph presentations in lessons more engaging, 85% agreed that the 3D features in Desmos help students grasp abstract concepts more concretely, 90% felt that Desmos Classroom facilitates real-time interaction through the online teacher dashboard, 80% noted that Desmos Classroom helps teachers assess student work, and 85% expressed their intention to use Desmos in their classroom teaching.